Bridging the Gap: Applying AI and Bayesian Statistics to Traditional Educational Leadership Training - Donoso Vargas, Diego José; Gallardo Cornejo, Ana María (European Public & Social Innovation Review, 2024)
Introduction: In the dynamic landscape of modern organizations, leadership is a vital competency. However, traditional uniform approaches often fail to address the diverse challenges posed by contemporary environments. Social, educational, and technological transformations, including the rise of artificial intelligence (AI), necessitate a shift toward more adaptive leadership styles. Methodology: This study explores situational leadership in higher education, focusing on its responsiveness to AI-driven resource management and its role in fostering professional success. Using Bayesian analysis, the study evaluates the effectiveness of project-based learning (PBL) in developing leadership qualities. Data from 404 educators across 28 institutions were analyzed, covering ten variables related to leadership and PBL. Results: The results offer insights into curricular development and educational strategies to equip students with essential skills for professional success. Discussion: Situational leadership, as developed by Hersey and Blanchard, emphasizes adapting leadership styles to follower maturity and specific situations, highlighting the need for flexibility in dynamic environments. Conclusions: The model's focus on follower maturity distinguishes it from static leadership models, underscoring its enduring relevance.